Blood Vessel, VEGF, and FGF Expression in Traumatic Ulcer Healing of Wister Rats after Application of Chitosan-Aloe vera Gel - Sularsih, Sularsih; Athaya, Yasmin Nabila; Rahmitasari, Fitria; Setianingtyas, Dwi; Priambodo, Nur Tsurayya; Riawan, Wibi (European Journal of Dentistry, 2025)
The purpose of this study was to analyze the application of chitosan (CH)-Aloe vera (AV) gel on blood vessels, vascular endothelial growth factor (VEGF), and fibroblast growth factor (FGF) expression in traumatic ulcer healing.Chitosan powder with deacetylation degree of 93% dissolved in 2% acetic acid, neutralized with NaOH solution, and combined with AV gel. Traumatic ulcers were made with a 4-mm diameter along the lower labial mucosa of Wistar rats using a heated burnisher. Negative control group (KA) was treated with placebo, positive control group (KB) using 0.2% hyaluronic acid, treatment group using chitosan (CH) gel (PA) and AV gel (PB), and group using combination CH-AV gel (PC). The blood vessel numbers were analyzed with hematoxylin eosin staining and the expression of VEGF and FGF were analyzed using immunohistochemistry on days 3 and 7.One-way analysis of variance was conducted to analyze the difference between groups and the Tukey honestly significant difference multiple comparisons test was used to analyze different pairs of groups (p < 0.05).Blood vessels, VEGF, and FGF expression were higher in the treatment group using combination CH-AV gel on days 3 and 7 compared with the control group and treatment group using CH or AV gel (p < 0.05).The application of CH-AV gel increased the number of blood vessels, VEGF, and FGF expression in traumatic ulcer healing of Wistar rats.
Keywords: chitosan; Aloe vera; traumatic ulcer healing; blood vessel; VEGF; FGF